The Impact of Surgery in IDH 1 Wild Type Glioblastoma in Relation With the MGMT Deregulation - Marchi, Francesco; Sahnane, Nora; Cerutti, Roberta; Cipriani, Debora; Barizzi, Jessica; Stefanini, Federico Mattia; Epistolio, Samantha; Cerati, Michele; Balbi, Sergio; Mazzucchelli, Luca; Sessa, Fausto; Pesce, Gianfranco Angelo; et al. (Frontiers in Oncology, 2020)
OBJECT. The treatment of choice in glioblastoma (GBM) is the maximal surgical extent of resection (EOR) followed by adjuvant chemo-radiotherapy. Furthermore, methylguanine-DNA methyltransferase (MGMT) promoter methylation is associated with prolonged overall survival (OS) and progression free survival (PFS). The objective of the present study is correlate the biomolecular aspects in relation with EOR. MATERIALS AND METHODS. We analyzed a series of 116 patients with IDH-1 wild type GBM and different EOR (Gross Total Resection – GTR-, Partial Resection –PR- and Biopsy), treated with adjuvant chemo-radiotherapy. The MGMT status was analyzed in terms of promoter methylation and protein expression. RESULTS. When GTR was possible, OS and PFS were significantly better compared to the other two groups (p=0.001 and p=0.035, respectively). MGMT methylation was significantly associated with better OS in the biopsy group (p=0.022) and better OS and PFS in PR (p=0.02 and p=.012, respectively), but not in the GTR group (p=0.252 for OS, p=0.256 for PFS) nor the PFS in the biopsy group (p=0.259). MGMT protein expression levels do not show any association with OS and PFS, regardless of the type of surgery. CONCLUSIONS. Our study confirms the positive association of a safe maximal EOR with better OS and PFS, and indicates a positive prognostic value of MGMT methylation status only in case of the presence of residual tumor tissue. MGMT protein expression seems not to play a clinical role in relation with the type of surgery.